Bridging Research and Practice: Translating Public Health Evidence into Policy Implementation in Gorontalo - Malasari, Puspita; Ardiansyah, Dewinta (Magenta Journal De Healthymedi, 2025)
The effective translation of public health research into policy implementation remains a significant challenge in many developing regions, including Gorontalo, Indonesia. This study aimed to explore the dynamics of social and ecological adaptation in the multi-level governance context of public health policy implementation. A mixed-methods approach was used, combining quantitative surveys with qualitative interviews and focus group discussions, to investigate community awareness, participation, and the role of governance structures in policy execution. The results revealed a significant gap between awareness of public health policies and active participation in health programs, exacerbated by limited resources, poor infrastructure, and a lack of coordination between national and local governments. Social and cultural barriers, such as traditional beliefs and gender norms, also impeded policy effectiveness. Furthermore, ecological challenges, such as flooding and inadequate sanitation, were found to worsen public health outcomes, hindering the success of health interventions. This study contributes to the existing literature by providing insights into the unique challenges faced in the implementation of public health policies in Gorontalo and offers practical recommendations for overcoming these obstacles. The study also emphasizes the need for more tailored, community-based approaches to health policy. Future research should focus on assessing the long-term impact of these policy interventions on health outcomes and community engagement.